Resilience and acculturative pathways underlying psychological well-being of immigrant youth. (January 2017) - Güngör, Derya; Perdu, Nora
Abstract: Most immigrant adolescents in Western Europe seem to feel well despite social-economic-cultural disadvantage. Researchers tend to relate the well-being of these youths to immigrants' distinctive experiences associated with their background culture, i.e., relatedness. Combining insights from resilience and acculturation perspectives in light of an ecological perspective, we tested the hypothesis that communal (e.g., school) and individual resources (e.g., autonomy) that highlight mainstream culture and values of independence are also conducive to the well-being of immigrant youth, especially when these youths are high on mainstream culture adoption. A questionnaire study among immigrant and nonimmigrant vocational school students in Belgium ( N  = 290) revealed that not only relatedness but also school engagement and autonomy were predictive of a high well-being of immigrant youth, particularly of those who adopted mainstream culture. Results suggest that in different cultural contexts acculturating youth rely on multiple resources to cope with social adversity and use acculturation orientations to maximize their benefit from these resources.